2020
DOI: 10.1111/eth.13019
|View full text |Cite
|
Sign up to set email alerts
|

Better safe than sorry: The response to a simulated predator and unfamiliar scent by the European hare

Abstract: Predator presence can create a “landscape of fear,” which is defined as the spatially explicit distribution of perceived predation risk as seen by prey. Prey species can alter their behavior and space use as a response to increased predation risk, which might be traded off with energetic requirements. Thus, whether or not an anti‐predator behavior is performed might depend on the perceived risk. In this study, we investigated the behavioral and spatial response of the European hare (Lepus europaeus) toward the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…In Central Italy, the red fox is mostly a fruit-consumer [ 60 , 71 , 72 ], although in some areas hares may play an important role in its diet, particularly where other food items are scarce [ 60 , 73 ]. Furthermore, foxes are perceived by brown hare as a threat, whatever the predation rate on this species [ 47 ]. Thus, outside the fenced area, the brown hare tends to use similar areas to those used by foxes, and both species are mostly nocturnal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Central Italy, the red fox is mostly a fruit-consumer [ 60 , 71 , 72 ], although in some areas hares may play an important role in its diet, particularly where other food items are scarce [ 60 , 73 ]. Furthermore, foxes are perceived by brown hare as a threat, whatever the predation rate on this species [ 47 ]. Thus, outside the fenced area, the brown hare tends to use similar areas to those used by foxes, and both species are mostly nocturnal.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in Turkey, activity rhythms of the Eurasian lynx Lynx lynx were temporally synchronized with those of the brown hare, supporting the brown hare as the main local prey species of the Eurasian lynx [ 44 ], although the authors did not test the effect of moon phases. Additionally, the presence of small carnivores, potential hare predators, has been suggested to alter the spatial behavior of this lagomorph, which shifts its spatial behavior to open areas with short vegetation where detection of potential predators is highest [ 45 , 46 ], or in areas rarely used by predators [ 47 ]. The European brown hare is reported to be mainly nocturnal, with activity peaking mostly in the first part of the night or in the crepuscular hours [ 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hares also adjusted space use on a finer scale, i.e. they remained further from field edges and spent more time in short vegetation, likely to have better visibility, thereby increasing the chance of detecting a potential approacher/predator (Focardi and Rizzotto 1999, Mayer et al 2020), also shown in other species (Lima 1992). In general, the spatial displacement and altered space use probably did not impede the hares' foraging efficiency as they spend more time in low vegetation which is of higher foraging quality (Wilmshurst et al 1995), though this effect was comparatively small.…”
Section: Discussionmentioning
confidence: 99%
“…For both these reasons, most biologgers transmitting data cannot transmit continuous data recorded at high rates. Rather, they provide, for example, 3 s bursts of data for every minute of operation, which allows a reasonable snapshot of the animal's biology [72] while accepting the holes in information that this entails. Ultimately, the utility of this approach depends on the questions being asked.…”
Section: Hardwarementioning
confidence: 99%